AJARAN SEJARAH ALAM NGADIRASA SEBAGAI PROSES INTERNALISASI KARAKTER/NILAI KOMUNITAS SUKU DAYAK BUMI SEGANDU INDRAMAYU - N. Fathurahman (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2019)
A belief, is not form, not born of vacuum, but will come from a variety of life experiences that are full of wonder, and have worldly dimensions. However, in practice, a belief requires a means to be able to read in the practice of everyday life. This study defines other communities with their disorders. By using the field-research method from the Mini Research assignment of Education Subjects at the UIN Sunan Gunung Djati Program Doktoral (S3), which is guided by Prof. Dr. H.M. Uus Ruswandi, M.Pd. and Dr. Hj. Aan Hasanah, Ph.D., where the community of the Dayak Bumi Segandu Losarang Indramayu Tribe is the object of study. The researcher separates other processes from a kebatinan community association that has the teachings of Nature as a process of internalizing the values / character of its followers.The results of the study show that for the community of the Dayak Bumi Segandu Losarang Indramayu, respecting fellow humans as natural beings is not easy for others and takes precedence in calling themselves a movement of patience and the first step in finding the truth. Then blame the Segandu Losarang Indramayu Earth Dayak community and its social roles have been united in the community, so that it can be part of the treasure of thought and also the value that characterizes the earth of Indonesian Unity in Diversity.